Correlation of Altered Expression of the Autophagy Marker LC3B with Poor Prognosis in Astrocytoma - Winardi, Daniel (Hindawi Publishing Corporation, 2014)
Glioblastoma multiforme is one of the most serious malignant brain tumors and is characterized by resistance to chemotherapy and radiation therapy. Recent studies suggest that autophagy may play an important role not only in the regulation of cancer development and progression but also in determining the response of cancer cells to anticancer therapy. The purpose of the present study was to assess the relationship between protein expressions of two autophagy markers, LC3B and Beclin-1, with clinical parameters in astrocytoma patients. Furthermore, the expression of CD133, a marker of the cancer stem-like cells, in astrocytoma patients was also investigated. A total of 106 thin-section slides were retrospectively collected from astrocytoma patients. LC3B, but not Beclin-1, protein expression was found to significantly correlate with resistance to radiation- or chemotherapy. In addition, high intensity of LC3B staining was predictive of poor prognosis. Furthermore, survival time of patients with high-level expression in both CD133 and LC3B was significantly shorter than those with weak expression in both CD133 and LC3B. These results suggest that astrocytoma cancer stem-like cells together with enhanced autophagy may cause resistance to radiation therapy/chemotherapy and that targeting the cancer stem-like cell in astrocytoma may offer a viable therapeutic approach.